Prognostic significance of aberrant CD5 expression in B-cell leukemia - Kaveh Jaseb; Daryush Purrahman; Saeid Shahrabi; Majid Ghanavat; Hadi Rezaeean; Najmaldin Saki (Frontiers Media S.A., 2019)
Aberrant expression of CD5 (as a T-cell marker) is seen in some leukemia and lymphoma of B lineage origin. Given that the signaling resulting from the expression of this marker plays an essential role in the development of leukemia and lymphoma, evaluating the expression of this marker is of paramount importance. Therefore, our goal in this study was to investigate the prognostic importance of CD5 expression in B-cell leukemia and lymphoma. We evaluate CD5 expression in normal and leukemic B-cells by identifying relevant literature through a PubMed search (1998-2018) of English language papers using the terms: 'CD5,' 'B-cell,' 'Leukemia,' and 'Lymphoma.' We are doing this thorough comparison of results from CD5 positive and negative cases to make a correct decision about prognostic importance of CD5 expression in these malignancies. In a number of B-cell malignancies, CD5 is expressed in varying degrees. Due to the different origins and characteristics of these malignancies, the results of CD5 expression evaluations are heterogeneous and impossible to generalize. However, CD5 expression is sometimes associated with clinicopathologic findings, more invasive clinical course, and even resistance to treatment (specifically in DLBCL) among CD5- positive patients, which appears to be a function of CD5 signaling and its downstream factors such as STAT3. Depending on the type of malignancy, CD5 expression is associated with good or bad prognosis, which can be used as an auxiliary prognostic factor to assess the clinical course of B-cell malignancies. Moreover, the difference in expression levels of CD5 in a variety of B-cell malignancies allows for differential diagnosis of these malignancies, which can be helpful when diagnosis is difficult.